PENGARUH INDUSTRI KECIL TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN SIDOARJO - Lina Absharina Fildzah; Raras Ardiningrum; Rusli Muhammad (Universitas Teuku Umar, 2021)
This study aims to determine the influence of small industries by covering several related indicators namely, business units, workers, production value of and the values of small industry investment on economic growth in Sidoarjo period 2010-2020. This type of research is quantitative descriptive using secondary data obtained from the publications of the Central Statistics Agency (BPS) of Sidoarjo Regency and the Department of Industry and Trade of Sidoarjo Regency. The study was conducted using multiple regression analysis using the E-views 12 Student Version application. The results obtained from the F test concluded that together, business units, workers, production values and small industrial investment values have great potential or are significant for economic growth, but partially have the most influence on economic growth. are production value and investment value. The result of the determinant coefficient test (R2) shows the ability of variable X (business unit, labor, production value and investment value of small industry) in explaining variable Y (economic growth) is 81.5 percent and the remaining 18.5 percent is influenced by factors other outside the variables studied.